Implementation of Wireless Sensor Network on Smart Trash Bins Using LoRa With AES128 Algorithm (Case Study: Mentari Waste Bank Panceng Gresik) - Hanafi, Nur; Yulianto , Ahmad Wilda; Rakhmania, Amalia Eka (Jurnal Jaringan Telekomunikasi, 2024)
Waste bank systems such as Bank Sampah Mentari (BSM), located in Prupuh, Panceng, Gresik Regency, were created as a method of reducing waste. In its operation, the BSM management still has several difficulties such as the need to check the resident’s shelters, to administrative problems that are still done manually. Based on these problems, the implementation of a wireless sensor network on a smart trash bin using LoRa with the AES128 algorithm was made. The way it works is that the node device sends sensor reading data to the gateway every hour. The gateway will describe the incoming data, then upload it to MySQL and firebase before being accessed in the application. The test shows that the system can run well according to the plan where the farthest distance of LoRa is 300 meters. The average RSSI generated by node 1 is -95.78 dBm, node 2 is -112.57 dBm, and node 3 is -117 dBm. HC-SR04 ultrasonic sensor testing has an error of 0.795% (accuracy of 99.205%), while the MAX17048 sensor has an error of 0.3% with accuracy of 99.7%.